Colleges of education science student engagement in Emergency Remote Teaching amidst COVID-19 in Nigeria - Bello Ganiyu (University of Muhammadiyah Malang, 2021)
There is paucity of studies on the affective, behavioural, and cognitive dimensions of student engagement under Emergency Remote Teaching (ERT) during COVID-19 pandemic, especially among pre-service science teachers in Colleges of Education in Nigeria. The purpose of this descriptive survey study was to examine the affective, behavioural, cognitive, and general level of engagement of pre-service science teachers in Colleges of Education in Kwara State, Nigeria in online ERT class. Purposive and snowballing sampling techniques were used to select six education colleges and 241 students which participated in the study respectively. The reliability coefficient of the online questionnaire used for data collection in the study was 0.81. The data gathered in this study were analysed using mean and independent t-test. The findings indicated that the level of student general engagement was high and there was significant gender difference in the levels of student behavioural engagement (X2(2) = 7.561, p = 0.023< .05) in favour of male students. It was concluded that Colleges of Education students’ level of affective, behavioural, cognitive, and general engagement in ERT was high. The researcher recommended that students should extend their high level of general engagement in online ERT class to face-to-face classes after COVID-19 pandemic.